Analisis Faktor Risiko yang Mempengaruhi Kejadian Obesitas pada Remaja: Studi Literatur - Karimah, Amani Shofi; Niarto, Zaskia Reihan Amanda; Lesmana, Dinda Annisa Putri; Faris, Ahlam; Herbawani, Chahya Kharin (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2025)
The prevalence of obesity in adolescents has significantly increased from 8% in 1990 to 20% in 2022. The World Health Organization (WHO) reports that more than 390 million children and adolescents aged 5 to 19 years are affected by obesity. This study aims to identify risk factors contributing to obesity in adolescents and is expected to help them avoid behaviors that could potentially lead to obesity. This literature review study utilizes the PRISMA guidelines and databases such as Google Scholar, Garuda, MDPI, PubMed, and ScienceDirect. Articles were searched using keywords in both Indonesian and English, such as